2021
DOI: 10.1371/journal.ppat.1009631
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell transmission of HSV1 in human keratinocytes in the absence of the major entry receptor, nectin1

Abstract: Herpes simplex virus 1 (HSV1) infects the stratified epithelia of the epidermis, oral or genital mucosa, where the main cell type is the keratinocyte. Here we have used nTERT human keratinocytes to generate a CRISPR-Cas9 knockout (KO) of the primary candidate HSV1 receptor, nectin1, resulting in a cell line that is refractory to HSV1 entry. Nonetheless, a small population of KO cells was able to support infection which was not blocked by a nectin1 antibody and hence was not a consequence of residual nectin1 ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…and fixed after 5 h. Cells were then either processed directly for immunofluorescence to stain only cell surface proteins or were permeabilized and stained to detect intracellular as well as cell surface protein. As previously shown in uninfected cells [27], nectin1 was localized to the cell surface of nTERT keratinocytes and the nectin1 antibody detected the protein at the cell surface, confirming that it recognized the extracellular domain of the protein (, mock). However, in HSV1-infected cells the characteristic cell surface pattern of nectin1 had disappeared by 5 h and nectin1 was not detectable within the permeabilized and stained cells, suggesting that nectin1 had been depleted during infection (, HSV1-GFP22).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…and fixed after 5 h. Cells were then either processed directly for immunofluorescence to stain only cell surface proteins or were permeabilized and stained to detect intracellular as well as cell surface protein. As previously shown in uninfected cells [27], nectin1 was localized to the cell surface of nTERT keratinocytes and the nectin1 antibody detected the protein at the cell surface, confirming that it recognized the extracellular domain of the protein (, mock). However, in HSV1-infected cells the characteristic cell surface pattern of nectin1 had disappeared by 5 h and nectin1 was not detectable within the permeabilized and stained cells, suggesting that nectin1 had been depleted during infection (, HSV1-GFP22).…”
Section: Resultssupporting
confidence: 81%
“…Cell surface staining of HSV1-GFP22-infected nTERT cells with an antibody for the transferrin receptor revealed that this receptor was present on the cell surface of both mock and infected cells at 5 h, and although the morphology of the cells had slightly changed in response to HSV1 infection, there was little or no downregulation of transferrin receptor (). In addition, staining of Wt-infected nTERT cells fixed at 4 and 8 h for the highly related protein nectin2, which we have previously shown does not function as an entry receptor for HSV [27], indicated that as for transferrin and in contrast to nectin1, nectin2 remained at the cell surface of HSV1-infected cells (). This suggests that HSV1 infection specifically targets nectin1 for downregulation from the cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations